Clinical and eeg analysis of mesial and lateral temporal lobe seizures - FÁBIO GALVÃO DANTAS; ELZA MÁRCIA T. YACUBIAN; CARMEN L. JORGE; CHRISTIANE C. PEDREIRA; JOAQUIM F. BUENO; ROSA M. F. VALÉRIO (Arquivos de Neuro-Psiquiatria)
The analysis of the temporal lobe seizures through video-EEG systems shows that they often consist of a sequence of clinical and EEG features which may suggest the localization and the lateralization of the epileptogenic lobe. We analyzed clinical and EEG features of 50 temporal lobe seizures which were separated in group 1 with 25 patients (related to mesial temporal sclerosis) and group 2 with 25 patients (other neocortical temporal lesions). Among the auras, the epigastric type was the most frequent and predominated in group 1. There were differences between the two groups, considering dystonic and tonic posturing and versive head and eye movements. Dystonic posturing was always contralateral to the ictal onset and was considered the most useful lateralizing clinical feature. Ictal speech, spitting and blinking automatisms, prolonged disorientation for place and a greatest percentage of postictal language preservation occurred in right temporal seizures. Postictal aphasia and global disorientation predominated in left temporal seizures. EEG was important for lateralizing the epileptogenic lobe, specially considering rhythmic ictal activity and postictal findings.